Migraine Associated with Gastrointestinal Disorders: Review of the Literature and Clinical Implications - van Hemert, Saskia; Breedveld, Anne C.; Rovers, Jörgen M. P.; Vermeiden, Jan P. W.; Witteman, Ben J. M.; Smits, Marcel G.; de Roos, Nicole M. (Frontiers in Neurology, 2014)
Recent studies suggest that migraine may be associated with gastrointestinal disorders, including irritable bowel syndrome, inflammatory bowel syndrome and celiac disease. Here an overview of the associations between migraine and gastrointestinal disorders is presented, as well as possible mechanistic links and clinical implications. People who regularly experience gastrointestinal symptoms have a higher prevalence of headaches, with a stronger association with increasing headache frequency. Children with a mother with a history of migraine are more likely to have infantile colic. Children with migraine are more likely to have experienced infantile colic compared to controls. Several studies demonstrated significant associations between migraine and celiac disease, inflammatory bowel disease and irritable bowel syndrome. Possible underlying mechanisms of migraine and gastrointestinal diseases could be increased gut permeability and inflammation. Therefore it would be worthwhile to investigate these mechanisms further in migraine patients. These mechanisms also give a rationale to investigate the effects of the use of pre- and probiotics in migraine patients.